Economic Valuation of the Nature tourism Area of Pulau Redang Marine Park, Terengganu, Malaysia - Mamat, Mohd Parid (2010)
Natural areas as recreational sites are increasingly recognized as important assets in conserving natural resources and generating economic growth via ecotourism development. The demand for tourism related to nature is quite substantial and is fast expanding. To cope with the increasing demand for ecotourism in Malaysia, the authorities need to provide adequate and high quality infrastructures. Decision-makers face difficulties in allocating scarce resources among competing uses. For recreational resources, it is not easy to obtain their monetary values because recreational experiences are not traded in the competitive market. Hence, with economic valuation of recreational resources that planners could rely on, more rational decisions or policies can be made for efficient management of resources. The purpose of the thesis is to estimate the values of Pulau Redang Marine Park (PRMP) in Malaysia, through users’ willingness to pay (WTP) and examine the perceptions and attributes of visitors’ satisfaction with the recreation facilities and services provided at PRMP. This study also evaluates the relationship between visitors’ characteristics and attributes of PRMP. In this study, the contingent-valuation method (CVM) was employed to estimate the economic value of conserving the marine park using the face-to-face interview technique. The WTP was elicited from a total of 308 respondents. The respondents were asked whether they would be willing to contribute a conservation fee to preserve PRMP as a recreational site. The average WTP for all respondents was estimated to range between RM10.86 and RM28.69 per visit. Using the total number of visitors to PRMP in 2008, a contribution of between RM1.6 million and RM4.3 million in aggregate was derived for the same year. In addition, there are the differences between the mean and median WTP for different models and also between foreign and local respondents. In all models, except for the log-normal model, the mean WTP values for foreign respondents are higher than the mean given by local respondents. The differences between the foreign and local WTP are larger with the mean WTP for foreign respondents being RM19.33 compared with that for local respondents of RM8.25 for the logistic model. In the log-logistic model the mean WTP for foreign respondents was RM13.12, while that for local respondents was RM10.73. For linear models, OLS and the Tobit, the mean WTP values for foreign respondents were RM12.59 and RM12.72, while the local respondents give RM7.06 and RM7.15 respectively. In recreation, visitors’ level of satisfaction with the facilities and services provided is also important in long-term ecotourism development. Most visitors to PRMP found the recreation facilities at a less satisfactory level. This is indicated by an average index of 1.55 for the recreation facilities evaluated which is below the intensity discrete value of 2.5 for positive perceptions. The visitors perceived the services provided at PRMP to be satisfactory with an average index of services of 2.77. The results also showed an overall perception index of 2.16. This means that the visitors who came and enjoyed PRMP were generally less satisfied with the recreational facilities provided. The study also showed that a total of six satisfaction attributes were significant predictors of overall satisfaction, accounting for 59 percent of the variance associated with overall satisfaction. This is a high amount of variance for a satisfaction model in the field of outdoor recreation. Of all the satisfaction attributes, efficiency of services, signs and directions/sign postings, locations of the facilities: convenience/setting, and freedom from obstruction by buildings/being in a natural place proved to be the best predictors of overall satisfaction. This shows that the management of PRMP should look at these items within specific recreation areas to ensure that they are meeting the visitors’ expectations. Perfecting these satisfaction attributes could help increase visitors’ overall experience, which could lead to repetition visits. The study also gathered information about the visitors’ perceptions, their expectations about the park and their assessments of its importance. They were asked to state their levels of satisfaction in terms of how they regard the destination by listing their own values. The majority of the respondents viewed the park as very valuable as a site for participating in recreational activities, with an average mean score of 4.00. Conservation was also important, as indicated by an average mean score of 3.83 for the conservation opportunities evaluated. The respondents agreed that PRMP should be conserved. The results are in line with the objective of establishing marine parks in Malaysia, i.e. to conserve and protect marine ecosystem and manage it for biodiversity research, educational purposes and the development of recreational and ecotourism activities that are sustainable. On their experiences while visiting the park, most of the respondents showed positive perceptions, indicated by an average mean score of more than 3.00 for the question asked. Being able to participate in the activities provided and enjoying the experiences with friends or family were the most satisfying things that they got from their trips to PRMP. This was followed by the feeling that the trips allowed them to escape from their normal routines and experience something new and different. That the trips allowed people to develop their own skills was the least important. On the visitors’ expectations of the park, most (94.8%) of the visitors regarded PRMP as a suitable site for recreation. In terms of crowdedness, the majority (87%) of the respondents said that the park was crowded and 79.9% of the respondents agreed that the park was attractive.